Electron-acoustic phonon field induced tunnel scattering - Melkonyan, S.V.; Harutyunyan, A.L.; Zalinyan, T.A. (Condensed Matter Physics, 2015)
Theory of electron-acoustic single phonon scattering has been reconsidered. It is assumed that the non-degenerate semiconductor has a spherical parabolic band structure. In the basis of the reconsideration there is a phenomenon of the tilting of semiconductor bands by the perturbing potential of an electric field. In this case, electron eigenfunctions are not plane waves or Bloch functions. In low-field regime, the expressions for electron intraband transition probability and scattering time are obtained under elastic collision approximation. Dependencies of scattering time on electron energy and uniform electric field are analyzed. The results of corresponding numerical computations for n-Si at 300 K are presented. It is established that there is no fracture on the curve of electron scattering time on the electron energy dependence. У статтi подано новий погляд на теорiю електронноакустичного розсiювання одного фонона. При цьому
припускається, що невироджений напiвпровiдник має сферичну параболiчну зонну структуру. В основу
перегляду теорiї покладено ефект нахилу напiвпровiдникових зон при накладаннi збурюючого потенцiалу електричного поля. У цьому випадку власнi функцiї електрона вже не є плоскими хвилями чи функцiями Блоха. В режимi слабких полiв отримано вирази для ймовiрностi електронних внутрiшньозонних
переходiв i для часу розсiяння в наближеннi пружнiх зiткнень. Також проаналiзовано залежнiть часу розсiяння вiд енергiї електрона та напруженостi однорiдного електричного поля. Представлено результати
вiдповiдних числових обчислень для n-Si при температурi 300 K. Встановлено вiдсутнiсть зламу на кривiй
залежностi часу розсiяння електрона вiд енергiї електрона.